What's the 411?: Assessing the Feasibility of Providing African American Adolescents with HIV/AIDS Prevention Education in a Faith-Based Setting - Francis, Shelley A. (Journal of religion and health, 2009)
This study examines African American faith based leaders' attitudes and beliefs about providing HIV prevention education and services to adolescents. Using a convenience sample, we identified priority adolescent health issues, attitudes about abstinence messages, and willingness to provide and participate in HIV prevention. Leaders identified drugs, gangs, alcohol, sex, and pregnancy as priority health issues affecting youth in their institutions. Leaders' strongly preferred to emphasize abstinence messages. Although leaders were willing to provide youth with health education, they were not willing to discuss specific behaviors associated with HIV transmission. African American churches provide a venue to reach African American youth; however, there are limitations to relying on faith-based HIV prevention services. HIV prevention education should continue to be supplemented via parents, schools, and public health agencies.